Lithium‐Ion Endohedral Fullerene (Li+@C60) Dopants in Stable Perovskite Solar Cells Induce Instant Doping and Anti‐Oxidation. (13th March 2018) - Jeon, Il; Ueno, Hiroshi; Seo, Seungju; Aitola, Kerttu; Nishikubo, Ryosuke; Saeki, Akinori; Okada, Hiroshi; Boschloo, Gerrit; Maruyama, Shigeo; Matsuo, Yutaka
Abstract: Herein, we report use of [Li + @C60 ]TFSI − as a dopant for spiro‐MeOTAD in lead halide perovskite solar cells. This approach gave an air stability nearly 10‐fold that of conventional devices using Li + TFSI − . Such high stability is attributed to the hydrophobic nature of [Li + @C60 ]TFSI − repelling moisture and absorbing intruding oxygen, thereby protecting the perovskite device from degradation. Furthermore, [Li + @C60 ]TFSI − could oxidize spiro‐MeOTAD without the need for oxygen. The encapsulated devices exhibited outstanding air stability for more than 1000 h while illuminated under ambient conditions. Abstract : Luftbeständigkeit ist die größte aktuelle Herausforderung bei der Kommerzialisierung von Perowskit‐Solarzellen. Konventionelle Li + TFSI − ‐Dotierung führt zu Problemen durch Hygroskopie. Fulleren‐verkapseltes Li + @C60 TFSI − ergibt 10‐mal luftstabilere Perowskit‐Solarzellen, da der Dotierstoff hydrophob ist, Spiro‐MeOTAD sofort oxidiert und antioxidativ wirkt.